Polymorphisms of the DNA repair genes XRCC1 and ERCC4 are not associated with smoking- and drinking-dependent larynx cancer in a polish population - Krupa, R.; Kasznicki, J.; Gajecka, M.; Rydzanicz, M.; Kiwerska, K.; Kaczmarczyk, D.; Olszewski, J.; Szyfter, K.; Blasiak, J.; Morawiec-Sztandera, A. (Experimental Oncology, 2011)
Aim of this article is to investigate the association between the genotypes of the XRCC1-Arg399Gln (rs25487) and ERCC4-Arg415Gln (rs1800067) polymorphisms and smoking- and drinking-related larynx cancer in a Polish population.